Determination of Poverty Levels in Jambi Province: A District/City Panel Data Approach - Rika Meliana Syahputri; Erni Achmad; Putri Intan Suri (Takaza Innovatix Labs Ltd., 2026)
Poverty remains a major development challenge in Jambi Province due to persistent poverty disparities between districts and cities, although the overall percentage of the poor population shows a downward trend. This study aims to analyze the development of the Human Development Index (HDI), the Open Unemployment Rate (TPT), population growth, and the poverty rate, and to examine the influence of these three variables on the poverty rate in Jambi Province. The study uses a quantitative approach with a panel data regression method. The study population covers all 11 districts and cities in Jambi Province, while the sample is determined using census techniques so that the entire population is used as the unit of analysis for the period 2020 to 2024. The research instrument consists of secondary data documentation obtained from the Jambi Province Central Statistics Agency and related publications. Data analysis includes descriptive analysis, panel data regression model selection, classical assumption tests, and hypothesis testing. The results show that the HDI has a negative and significant effect on the poverty rate, population growth also has a negative and significant effect, while the Open Unemployment Rate has no significant effect. Simultaneously, all independent variables have a significant effect on the poverty rate. In conclusion, improving the quality of human development is a major factor in reducing poverty in Jambi Province, while poverty alleviation policies need to be integrated with equitable development and strengthening regional economic capacity